SENSIVITAS GENDER HAKIM BANDING DALAM PUTUSAN KEKERASAN DALAM RUMAH TANGGA - Fitriyani, Fitriyani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2021)
This study found that judges' sensitivity to gender issues was still low in the Religious High Court, especially in deciding cases related to husband and wife issues. This is due to the judge's understanding of legal sources and the ability of judges to use legal logic which is still gender-biased. This research is a qualitative study (library research) with descriptive-analytical character, using a juridical approach and a gender approach, in which the researcher will describe and analyze according to the data obtained, in relation to court decisions regarding Domestic Violence (KDRT) using the main data source. namely in the form of decisions of the High Religious Courts related to Domestic Violence (KDRT) taken from the website of the Supreme Court of the Republic of Indonesia, secondary, primary, and tertiary data and judge interviews as supporting data for the study. Data analysis uses content analysis of court decisions related to Domestic Violence (KDRT). Aims to understand the logic of the judge's decision and analyze the judge's argument on the decision on Domestic Violence (KDRT) from the perspective of gender justice in the Religious High Court. There are three aspects used by judges in deciding cases: 1) legal aspects, 2) philosophical aspects, and 3 social aspects. In addition to these three aspects, judges also use legal logic/judges' ijtihad in the discovery of new laws. The perspective of judges' decisions that are not gender-equitable are characterized by the presence of 1) marginalization of women, 2) subordination, 3) stereotypes, 4) violence, 5) double burden.